2010
DOI: 10.1038/sj.bjc.6605736
|View full text |Cite|
|
Sign up to set email alerts
|

BCL2 in breast cancer: a favourable prognostic marker across molecular subtypes and independent of adjuvant therapy received

Abstract: Background:Breast cancer is heterogeneous and the existing prognostic classifiers are limited in accuracy, leading to unnecessary treatment of numerous women. B-cell lymphoma 2 (BCL2), an antiapoptotic protein, has been proposed as a prognostic marker, but this effect is considered to relate to oestrogen receptor (ER) status. This study aimed to test the clinical validity of BCL2 as an independent prognostic marker.Methods:Five studies of 11 212 women with early-stage breast cancer were analysed. Individual pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
234
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(257 citation statements)
references
References 40 publications
19
234
0
4
Order By: Relevance
“…This is consistent with the results obtained previously (Park et al, 2002;Neri et al, 2006), which indicate that the expression of Bcl-2 is a marker of breast cancer with reduced capability of distant colonization even in presence of lymphovascular invasion (Neri et al, 2006). On the contrary, Nadler et al (2008), found no association between expression of Bcl-2 and nodal status and Dawson et al (2010), verified the prognostic impact of Bcl-2 positivity regardless of lymph node status.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with the results obtained previously (Park et al, 2002;Neri et al, 2006), which indicate that the expression of Bcl-2 is a marker of breast cancer with reduced capability of distant colonization even in presence of lymphovascular invasion (Neri et al, 2006). On the contrary, Nadler et al (2008), found no association between expression of Bcl-2 and nodal status and Dawson et al (2010), verified the prognostic impact of Bcl-2 positivity regardless of lymph node status.…”
Section: Discussionsupporting
confidence: 91%
“…This is not surprising because a recent study proved that Bcl-2 is a prognostic factor in women with both ER positive and ER negative disease and also in women with both Her2 negative and Her2 positive disease and its positivity is maintained across various molecular subtypes of breast cancer (Dawson et al, 2010). Although the frequency of Bcl-2 expression ranged from 69-73% in previous studies (Dawson et al, 2010;Kallel-Bayoudh et al, 2011), a controversy exists because they found that TNBC tend commonly to have lower Bcl-2 expression compared to non-TNBC (Tawfik et al, 2010;de Ruijter et al, 2011), moreover, Bcl-2 oncogene expression was found to be statistically greater in the ER positive breast tumors compared to ER negative tumors (dos Santos et al, 2008). Such discrepancies between the studies are likely to be due to the wide variation between the methodologies and types of cases studied (Cecka et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It was previously reported that GATA-3 functions as a critical regulator of commitment and maturation of cancer cells in the luminal A epithelial lineage, i.e., the expression of GATA-3 regulates luminal differentiation (37). The anti-apoptotic marker Bcl-2 has been proven to be an independent molecular signature, alone or in combination with Ki-67 as a marker pair, in the luminal type of breast cancer (38)(39)(40)(41)(42).…”
Section: Luminalmentioning
confidence: 99%